HEALTH EXPENDITURES AND EDUCATION EXPENDITURES RELATED TO LABOR PRODUCTIVITY IN INDONESIA? A TIME SERIES ANALYSIS SPANNING 2001–2019 - Rosdiana Sijabat (Insan Doktor Ekonomi Indonesia (IDEI), 2026)
This study examined government health and education spending and its impact on Indonesian labor productivity from 2001 to 2019. The problem was relevant since Indonesia's labor productivity rose before 2019, while health and education spending fluctuated. Labor productivity rose from 4.38 in 2001 to 11.84 in 2019, while government health expenditure rose from 3.96% to 8.67% of general government expenditure. Government education spending rose from 11.59% of general government spending in 2001 to 17.35% in 2019 but fluctuated thereafter. These patterns raised the question of whether Indonesian labor productivity was improved by public spending on education and health. This study used secondary data from 2001 to 2019 for quantitative time-series analysis. Descriptive analysis, Augmented Dickey-Fuller and Phillips-Perron unit root tests, Johansen and cointegration test, and regression analysis were used. Results revealed that health spending boosted labor productivity in the short and long term. Education expenditure had little short-term effect but a favorable and large long-term benefit. These findings suggested that health investment boosted labor productivity faster than education spending. Thus, Indonesian policy should increase health and education spending and improve the quality and effectiveness of these expenditures to boost human capital and labor productivity. Studi ini mengkaji dampak belanja kesehatan dan pendidikan pada produktivitas tenaga kerja Indonesia dari tahun 2001 hingga 2019. Studi ini signifikan karena produktivitas tenaga kerja Indonesia meningkat sebelum tahun 2019, sementara belanja untuk kesehatan dan pendidikan berfluktuasi. Produktivitas tenaga kerja meningkat dari 4,38 pada tahun 2001 menjadi 11,84 pada tahun 2019, sementara belanja pemerintah untuk kesehatan meningkat dari 3,96% menjadi 8,67% dari belanja pemerintah umum. Belanja pemerintah untuk pendidikan meningkat dari 11,59% dari belanja pemerintah umum pada tahun 2001 menjadi 17,35% pada tahun 2019 tetapi berfluktuasi setelahnya. Kondisi ini menimbulkan pertanyaan apakah produktivitas tenaga kerja Indonesia meningkat akibat belanja pendidikan dan kesehatan. Studi ini menggunakan data sekunder dari tahun 2001 hingga 2019 untuk analisis deret waktu. Analisis deskriptif, uji akar unit Augmented Dickey-Fuller dan Phillips-Perron, uji Johansen dan kointegrasi, serta analisis regresi digunakan untuk menjawab tujuan penelitian. Hasil penelitian menunjukkan bahwa belanja kesehatan meningkatkan produktivitas tenaga kerja dalam jangka pendek dan panjang. Belanja pendidikan memiliki sedikit pengaruh jangka pendek tetapi memberikan manfaat jangka panjang. Temuan ini menunjukkan bahwa investasi kesehatan meningkatkan produktivitas tenaga kerja lebih cepat daripada belanja pendidikan. Oleh karena itu, kebijakan peningkatan belanja kesehatan dan pendidikan perlu disertai kualitas dan efektivitas belanja untuk meningkatkan produktivitas tenaga kerja.